Gas infall and radial transport in cosmological simulations of milky way-mass discs. Issue 3 (10th November 2021) - Trapp, Cameron W; Kereš, Dušan; Chan, Tsang Keung; Escala, Ivanna; Hummels, Cameron; Hopkins, Philip F; Faucher-Giguère, Claude-André; Murray, Norman; Quataert, Eliot; Wetzel, Andrew
ABSTRACT: Observations indicate that a continuous supply of gas is needed to maintain observed star formation rates in large, discy galaxies. To fuel star formation, gas must reach the inner regions of such galaxies. Despite its crucial importance for galaxy evolution, how and where gas joins galaxies is poorly constrained observationally and rarely explored in fully cosmological simulations. To investigate gas accretion in the vicinity of galaxies at low redshift, we analyse the FIRE-2 cosmological zoom-in simulations for 4 Milky Way mass galaxies ( M halo ∼ 10 12 M ⊙ ), focusing on simulations with cosmic ray physics. We find that at z ∼ 0, gas approaches the disc with angular momentum similar to the gaseous disc edge and low radial velocities, piling-up near the edge and settling into full rotational support. Accreting gas moves predominately parallel to the disc and joins largely in the outskirts. Immediately prior to joining the disc, trajectories briefly become more vertical on average. Within the disc, gas motion is complex, being dominated by spiral arm induced oscillations and feedback. However, time and azimuthal averages show slow net radial infall with transport speeds of 1–3 km s −1 and net mass fluxes through the disc of ∼M⊙ yr −1, comparable to the galaxies' star formation rates and decreasing towards galactic centre as gas is sunk into star formation. These rates are slightly higher in simulations without cosmic rays (1–7 km s −1, ∼4–5 M⊙ yr −1 ). We find overall consistency of our results with observational constraints and discuss prospects of future observations of gas flows in and around galaxies.